ETIKA HINDU DALAM REPRESENTASI SENI BONDRES DI KOTA SINGARAJA BALI - Wayan Sunampan; Nyoman Suardika (STAH Dharma Sentana Sulawesi Tengah, 2021)
The results of this study discuss the form of bondres art representation in the city of Singaraja with an ethical perspective, and focus on several bondres sekaa in the city of Singaraja. This research is a qualitative type with the process of collecting data through observation, interviews, documentation, and online data searches. The data obtained were then analyzed and then presented with a qualitative descriptive. The results of the study show that Bondres art is represented by several things including 1) Characters, 2 Clothing, 3) Plays. The form of representation of Bondres art shows that there is an ethical aspect where Bondres art is used as an educational medium to instill moral values. Although sometimes there is an unethical impression either from the clothes or the dialogue that is delivered.